Mental health of polish immigrants in Iceland - Aleksandra Agata Knasiak 1999- (2024)
Studies have shown that immigrants face a lot of challenges regarding mental health, social support and employment. This study explores mental health among Polish immigrants. A total of 243 participants, 18 years and older, participated in the study. The data collecting was done through an online questionnaire which included questions about age, gender, the length of living in Iceland, experience with psychological services, social support and mental health. The results revealed that Polish immigrants in Iceland have on average moderate scores in mental well-being, depression, anxiety and stress. However, 50.6% of the participants had stated that their mental health had gotten worse since moving to Iceland. Nearly 32% of the participants had sought psychological support of whom most had done so through the internet with a Polish speaking psychologist. Increased levels of social support were associated with higher mental well-being scores and lower depression, anxiety and stress scores (p < 0.01). Those who were unemployed experienced significantly more stress than those employed (p = 0.038). This study provides insight into the mental health of Polish immigrants in Iceland and potential influential factors. Fyrri rannsóknir hafa sýnt að innflytjendur standa frammi fyrir áskorunum varðandi andlega heilsu, félagslegan stuðning og atvinnu. Þessi rannsókn skoðar andlega heilsu pólskra innflytjenda á Íslandi. Alls tóku 243,18 ára og eldri, þátt í rannsókninni. Gögnum var safnað með rafrænum spurningalista sem innihélt spurningar um kyn, aldur, lengd búsetu á Íslandi, reynslu af sálfræðiþjónustu, félagslegan stuðning og andlega heilsu. Niðurstöðurnar sýndu að pólskir innflytjendur á Íslandi upplifa, að meðaltali, miðlungs andlega vellíðan, þunglyndi, kvíða og streitu. Samt sem áður töldu 50,6% þátttakenda að andleg heilsa þeirra hafði versnað síðan þeir fluttu til Íslands. Um 32% þátttakenda höfðu leitað sér sálfræðiaðstoðar en flestir höfðu sótt sálfræðiþjónustu í gegnum netið hjá pólskumælandi sálfræðingi. ...